Application of RAPD-PCR for DNA-Fingerprinting of Egyptian Tilapia - H. Soufy; A. M. Laila; M. K. A. Iman (New Visions in Science and Technology Vol. 1, 2021)
In this investigation, RAPD-PCR was used to examine the DNA-fingerprint and the similarity among three tilapia fish in Egypt, Oreochromis niloticus, Sarotherodon galilaeus and Tilapia zilli. Evaluate of common patterns of genetic variations or similarities among three species of tillapine through the DNA fingerprinting analysis was performed in this study using RAPD-PCR (Random amplified polymerase chain reaction) using 10 arbitrary primers, out of 10 primers used, 7 primers gave strong sharp distinct bands. The 7 primers produced atotalof 15, 13, 16, 14, 18, 14 and 17 bands respectively. Depending on the similarity coefficient through the used primers, the similarity between Oreochromis niloticus and Oreochromis galilaius was 95% and between Oreochromis niloticus and Tilapia zilli was 80% and between Oreochromis galilaius and Tilapia zilli was 75%. The values of the genetic distances obtained were utilized to generate a distance matrix to construct a dendrogram which linked the studied species. The results of DNA fingerprinting of the studied fishes can be taken into consideration as a joint patterns of similarity and probability of Hybridization between the very closed species to improve the genetic characters. It can be concluded also that, RAPD-PCR could prove to be a useful tool for estimating the genetic variability and degree of similarity among fish species.